Implementation of Guidance Services in the Basic Education Department of Tomas Claudio Colleges - Toledo, John Joshua (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of guidance services in the Basic Education Department of Tomas Claudio Colleges during School Year 2025–2026. Specifically, it assessed the extent of implementation of individual inventory service, information service, counseling service, and follow-up service, as perceived by teacher-respondents and Grade 12 student-respondents. It also determined whether significant differences exist in their perceptions when grouped according to their profile variables and identified the common problems encountered in the implementation of guidance services.A descriptive survey research design was utilized. The respondents were composed of all senior high school teachers (n=15) and all Grade 12 students (n=247). Data were gathered through a researcher-made questionnaire checklist. Descriptive and inferential statistical tools were employed to analyze the data.Findings revealed that teacher-respondents were mostly 31 years old and above, female, married, pursuing graduate studies, with 5–9 years of service, holding Teacher I and II positions, and had attended various in-service trainings. Student-respondents were mostly female, second or third-born children, coming from families with two or more siblings, with a monthly family income of ₱25,000 and above, and parents who were college graduates and employed. As perceived by teachers, individual inventory service was very much implemented, while information, counseling, and follow-up services were much implemented. Students generally perceived all services as much implemented. A significant difference was found between teachers’ and students’ perceptions in terms of individual inventory and follow-up services, while no significant difference was observed in information and counseling services. Differences in perceptions were also noted among students in terms of parents’ educational attainment and occupation. Identified problems included low student engagement in follow-up activities, limited parental involvement, and inadequate dissemination of guidance information.The study concludes that perceptions on guidance service implementation vary between teachers and students in selected areas, highlighting the need for improved communication and stakeholder involvement.